FoxO1 controls lysosomal acid lipase in adipocytes: implication of lipophagy during nutrient restriction and metformin treatment - Lettieri Barbato, D (Nature Publishing Group, 2013)
Finding new molecular pathways and strategies modulating lipolysis in adipocytes is an attractive goal of the current research. Indeed, it is becoming clear that several human age-related pathologies are caused by adipose tissue expansion and altered lipid metabolism. In the present work, we show that transcription factor forkhead homeobox type protein O1 (FoxO1) is upregulated by nutrient restriction (NR) in adipocytes and exerts the transcriptional control of lipid catabolism via the induction of lysosomal acid lipase (Lipa). An increased autophagy and colocalization of lipid droplets (LDs) with lysosomes was observed implying lipophagy in Lipa-mediated LDs degradation. Interestingly, we found that metformin (Metf), a biguanide drug commonly used to treat type-2 diabetes, exerts effects comparable to that of NR. Actually, it was able to elicit FoxO1-dependent Lipa induction as well as LDs degradation through lipophagy. Moreover, we demonstrate that, during NR or Metf treatment, free fatty acids released by Lipa are directed toward AMP-activated protein kinase-mediated mitochondrial oxidation, thus maintaining energetic homeostasis in adipocytes. In conclusion, our data show that lysosomal-mediated lipid catabolism is activated by NR in adipocytes and give further support to the use of Metf as a NR mimetic to combat age-related diseases associated with altered lipid metabolism.